Peranan Tabligh Sebagai Sarana dalam Meningkatkan Kemampuan Public Speaking Di Pesantren Al-Mukhtariyah Sungai Dua Kecamatan Portibi - Arofah Sri Mulyani Mz; Azhar (STAI Bumi Silampari, 2025)
The purpose of this study was to determine the role of Tabligh in improving public speaking skills at the Al-Mukhtariyah Sungai Dua Islamic Boarding School. Tabligh, which comes from Arabic which means to convey, is used for preaching and developing communication skills. Based on the theory of preaching communication and constructivism, this study shows that Tabligh activities not only function as a medium for preaching, but also as a forum to train students to speak in public, both in the Islamic boarding school environment and in society. This research method uses a qualitative approach with observation, interview, and documentation techniques for administrators, students, and teachers who actively participate in Tabligh activities. The results of the study showed that students who initially felt nervous and insecure when speaking in public, are now more adept at delivering speeches, poems, and preaching materials. This study concludes that Tabligh activities at the Al-Mukhtariyah Sungai Dua Islamic Boarding School play an important role in developing students' communication skills, this is in line with the educational goals of Islamic boarding schools to produce cadres of students who are able to communicate effectively and have noble morals.